Treatment Outcomes of Sinonasal Malignancies Involving the Orbit - Shin, Chul Ho; Lee, Ho Jun; Chung, Yoo-Sam; Kim, Ji Heui (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Orbital invasion is associated with a poor prognosis in cases of sinonasal malignancy. This study aimed to analyze the oncological outcomes of sinonasal malignancies involving the orbit.Patients and Methods We reviewed the medical records of 116 patients with a sinonasal malignancy who had orbital invasion at initial diagnosis and followed up at least 6 months between June 1991 and October 2017 at a single institute. The overall survival (OS), disease-specific survival (DSS), and progression-free survival (PFS) rates according to the clinicopathological factors, extent to orbit, and treatment modality were compared.Results Patients were mainly treated with surgery and postoperative radiation (n = 39, 33.6%) and concurrent chemoradiation (n = 72, 62.1%). Only five patients (5.1%) underwent orbital exenteration. The OS, DSS, and PFS rates significantly decreased in patients older than 60 years of age and in patients with a higher Charlson Comorbidity Index Score (each p < 0.001). The OS and DSS rates were higher in patients at clinical T3 and N0 stage than in patients at clinical T4 and N1–2 stage (each p < 0.05). There were no significant differences in survival and local control rates according to the extent of orbital invasion, treatment modalities, and orbital preservation. However, neoadjuvant chemotherapy and adjuvant radiation or concurrent chemoradiation increased survival rates in the patients treated with surgery.Conclusion Orbit preservation and relatively successful oncological outcome could be obtained with surgery and adjuvant radiation or concurrent chemoradiation.
Keywords: sinonasal malignancy; orbit; surgery; radiotherapy; chemoradiotherapy; survival